2016
DOI: 10.1007/s10750-016-3031-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of predation in biological communities in naturally eutrophic sub-Arctic Lake Mývatn, Iceland

Abstract: Effects of fish predation on consumers tend to be particularly strong in oligotrophic Arctic and sub-Arctic lakes. However, it remains unclear whether the fish influence the trophic structure and dynamics of naturally eutrophic lakes in these cold environments with simple food web structures. To study this, we conducted a 3-month in situ-controlled experiment in sub-Arctic Lake Mývatn, Iceland. We used the planktivorous fish three-spined sticklebacks (Gasterosteus aculeatus) as the main top predator. The clado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Moreover, some studies have suggested that because Anabaena can grow under low N conditions, blooms are related to the naturally low N:P levels in the incoming spring water to the lake (Jonasson & Adalsteinsson, 1979). Anabaena blooms also appeared during our mesocosm experiment (Cañedo-Arg€ uelles et al, 2017).…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…Moreover, some studies have suggested that because Anabaena can grow under low N conditions, blooms are related to the naturally low N:P levels in the incoming spring water to the lake (Jonasson & Adalsteinsson, 1979). Anabaena blooms also appeared during our mesocosm experiment (Cañedo-Arg€ uelles et al, 2017).…”
Section: Introductionmentioning
confidence: 62%
“…Most studies have focused on the abundance, biomass, or average size of predators and prey (Knight, McCoy, Chase, McCoy, & Holt, 2005;Pace, Cole, Carpenter, & Kitchell, 1999). Size-based interactions between predators and prey at adjacent trophic levels in the food web have often not been considered, despite that they play a key role in the trophic structure and functioning of aquatic ecosystems (Brose et al, 2006;Brown, Gillooly, Allen, Savage, & West, 2004;Brucet et al, 2017;Emmerson & Raffaelli, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations